Learning Model Based on Multiple Intelligence in Stimulating Musical Intelligence in Children - Anada Leo Virganta; Kamtini Kamtini; Nurmaniah Nurmaniah; Salsabila Hasiana Tanjung (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Every child has different characteristics with different ways of learning. Children tend to have a very active nature because they have seen muscle development that allows them to perform a variety of skills. By using learning based on multiple intelligence, children are more stimulated to carry out the learning process and significant development achievements are achieved. This study uses a development research method by conducting time-series tests on data processing. The population used is children aged five to six who are in kindergarten age, namely children aged in five until six years. Children show a good increase in the stimulation of musical intelligence using a learning model that has been developed. The novelty of this research is to produce and use a learning model based on multiple intelligences that children have. But still, focus on stimulating children's musical intelligence.